Influence of tax knowledge, socialization, and sanction on the decision to participate in the voluntary disclosure program with intention as an intervening variable: A case study at Palembang Ilir Timur tax office - Irfandhani, Reza; Sulastri; Maulana, Ahmad; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2023)
This research investigates the influence of tax knowledge, tax socialization, and tax sanctions on the decision to participate in the Voluntary Disclosure Program with Interest as an intervening variable at the East Ilir Palembang Pratama Tax Service Office. One hundred respondents completed questionnaires at the East Ilir Palembang Pratama Tax Service Office. The Partial Least Square Structural Equation Model (SEM-PLS) was the analysis technique. The findings indicate that tax socialization positively and significantly impacts Interest and the decision to participate in the Voluntary Disclosure Program. Other variables, such as tax knowledge and tax sanctions, were found to have no significant influence on Interest and the decision to participate in the Voluntary Disclosure Program. Notably, Interest directly influences the decision to participate in the Voluntary Disclosure Program positively and significantly. It is hoped that this research can be a reference for future research in terms of using variables for similar research.